ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA PT. BANK SUMUT KCP AKSARA MEDAN - Siregar, Lisma Yana; Harahap, Muhammad Ihsan (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Employees or employees are the main resource of a company because employees are the determining factor in achieving company goals through employee performance. There were many factors that influenced employee performance in this study, and the factors analyzed were leadership, motivation, communication, and employee performance. In order to improve employee knowledge and skills, one of the efforts made by the company is to maximize education, empowerment, service orientation, appreciation and training of its employees. If one of them is not fulfilled, there will be problems and the impact is mismanagement and company losses. The results showed that some leadership variables had a positive and significant effect on employee performance. In the research area, organizational culture has proven to be a moderator between leadership and employee performance at the SUMUT Aksara Bank Branch.